Bank-sovereign ties against interbank market integration: The case of the Italian segment - Susanna Saroyan; Lilit Popoyan (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
This paper investigates interbank market fragmentation that results from the bank-sovereign risk nexus. We focus on the Italian market fragmentation during the post-Lehman and sovereign debt crisis era. By using Italian bank and GIPSI country CDS spread changes, we suggest a new measure of sovereign/bank spillovers, based on partial correlations. Then, we examine the relationship between the sovereign-to-banks contagion risk variable and market fragmentation in rate on the e-MID interbank market data. We find that the bank-sovereign nexus is a signicant source of fragmentation during the most acute phase of the sovereign debt crisis. Our findings suggest that even if the home country/bank ties impact interbank market integration seriously, the risk from other distressed countries is not negligible.
Keywords: E42; E58; G21; G28; 330; Money market fragmentation; sovereign risk; sovereign-bank spillover; contagion; bank regulation